Economic diversity and the resilience of cities - François de Soyres; Simon Fuchs; Illenin O. Kondo; Helene Maghin (Federal Reserve Bank of Atlanta, 2025)
We show how local worker flow adjustment margins yield a theory-consistent sufficient statistic approximating the welfare effects of local shocks. Furthermore, we isolate a city's insurance value as this approximation's second-order term. Leveraging rich labor flows data across occupations, industries, and cities in France, we estimate spatial and nonspatial flows responses to local labor demand shocks. Less economically diverse French cities experience deeper contractions in gross outflows following negative shocks. In contrast, more economic concentration begets a modestly larger increase in gross worker flows following positive shocks. Altogether, we uncover sizable welfare insurance gains from local economic diversity.
Keywords: J61; J62; J21; 330; sufficient statistic; labor flows; concentration; economic diversity; welfare